Violence and Moral Exclusion: Legitimizing Domestic Military Operations in Brazil - Junior, David P. Succi [UNESP] (SAGE Publications, 2021)
Many contemporary security issues entail the domestic military deployment, which is deemed to blur the division between armed forces and police. This argument relies on the theoretical coalescence between territory, political authority, and community. In contrast, I argue the military domestic deployment is largely grounded on the process of defining and redefining the boundaries of the community to be protected, which informs the organization of the instruments of force and is shaped throughout the process of legitimizing a particular kind of violence deployment. This article analyses the parliamentary minutes on three domestic military operations in Brazil—Operation Rio (1994), Operation Arcanjo (2010), and the Operation Rio de Janeiro (2017)—through the moral exclusion framework and shows that the debates about whether or not the armed forces should be deployed are embedded in the struggle of drawing the community’s boundaries.
Keywords: civil military relations; defense policy; international relations; policing; South Central America